DOI: 10.3990/1.9789036546270
|View full text |Cite
|
Sign up to set email alerts
|

Infrared carbonate rock chemistry characterization

Abstract: INFRARED CARBONATE ROCK CHEMISTRY CHARACTERIZATION DISSERTATION to obtain the degree of doctor at the University of Twente, on the authority of the rector magnificus, prof.dr. T.T.M. Palstra, on account of the decision of the graduation committee, to be publicly defended on Thursday October 4, 2018 at 14.45 hrs First and foremost, I must praise and thank Almighty Allah, the Lord of the worlds, the Most Gracious and the Most Merciful, who gave me the infinite blessing, guidance and ability to successfully compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 121 publications
(536 reference statements)
1
0
0
Order By: Relevance
“…These results converged with (Zaini & Ghagari, 1989) who reported 45.6% for tinea capitis, and with (Gargoom et al, 2000) who reported 45% for tinea capitis, but are higher than the results of (Amer, Taha, Vet, Zeinab Tosson, & El-Carf, 1981) who reported 36%, and (Shtayeh & Arda, 1985) who reported 38.7 % .…”
Section: Discussionsupporting
confidence: 79%
“…These results converged with (Zaini & Ghagari, 1989) who reported 45.6% for tinea capitis, and with (Gargoom et al, 2000) who reported 45% for tinea capitis, but are higher than the results of (Amer, Taha, Vet, Zeinab Tosson, & El-Carf, 1981) who reported 36%, and (Shtayeh & Arda, 1985) who reported 38.7 % .…”
Section: Discussionsupporting
confidence: 79%